PENERAPAN PENDIDIKAN KARAKTER DALAM MENGURANGI PERILAKU MENYIMPANG SISWA DI SMA NEGERI 2 LHOKSEUMAWE - A Marliah; M Nazaruddin; M Akmal (FISIP Universitas Malikussaleh, 2020)
This study focuses on two discussions. First, to describe the application of character education at SMA Negeri 2 Lhokseumawe. Second, to describe the obstacles in the application of character education so that it is not effective in overcoming student deviant behavior. By using a qualitative approach, this study comes to an understanding that the implementation of character education in SMA Negeri 2 Lhokseumawe is carried out through several strategies, including: a). providing outreach to teachers; b). preparation of syllabus and lesson plans based on character education; c). integrating and applying values in the teaching and learning process in the classroom; d) creating a school culture; e) habituation; and f) teacher exemplary. The implementation of character education in order to reduce students' deviant behavior has not been optimal because it faces a number of obstacles, such as a) minimal family contribution; b) inconsistency of values and norms at school and outside school; and c) teachers' difficulties in adapting to curriculum changes. In addition, the definition of deviant behavior and social dysfunction has so far only relied on